Research on trajectory planning of closed loop grouting robot. (November 2021) - Zhang, Runmei; Ren, Rui; Luo, Guan; Li, Shuai; Bi, Lijun; Yuan, Bin
In order to promote building intelligence and solve the disadvantages of traditional grouting technology, the trajectory planning of closed-loop grouting robot was designed. The minimumsnap optimization function was used to optimize the A* algorithm to realize the 2D trajectory planning, which could obtain a smooth, continuous route, and planning diagram of time distribution, speed, acceleration, and jerk. Further, the weight function of the improved A* algorithm was adjusted to perform 3D trajectory planning to reduce redundant nodes in the route. A new approaching law adaptive sliding mode control method was used to achieve precise trajectory tracking of the robotic arm and reduce the problem of chattering in sliding mode control. Through the design of closed-loop grouting robot and the research of trajectory planning, the two-dimensional and three-dimensional paths of grouting robot could be optimized. The system could realize automatic grouting operation. It could promote the development of high efficiency and safety in the construction grouting industry.